Capturing natural resource heterogeneity in top-down energy-economic equilibrium models - Rausch, Sebastian; Zhang, Da (Energy economics, 2018)
Top-down energy-economic modeling approaches often use simplified techniques to represent heterogeneous resource inputs to production. We show that for some policies, such as feed-in tariffs for renewable electricity, detailed representation of renewable resource grades is required to describe the technology more precisely and identify cost-effective policy designs. We demonstrate the hybrid approach for modeling heterogeneity in the quality of natural resource inputs required for renewable energy production in a stylized computable general equilibrium framework. Importantly, compared to the traditional approach, the hybrid approach resolves near-flat or near-vertical sections of the supply curve and improves the precision of policy simulation. We then represent the shape of a resource supply curve based on more detailed data. We show that for the case of onshore wind development in China, a differentiated feed-in tariff design that can only be modeled with the hybrid approach requires less than half of the subsidy budget needed for a uniform feed-in tariff design to achieve the same installation targets.
Gesehen am 24.04.2023